(untitled) (Jurnal Manajemen dan Ekonomi (JME), 2024)
This research aims to analyze the financial policies put forward in the Arthasastra, a classic work on economics and politics written by Kautilya in the 4th century BC, and explore its relevance and application in the contemporary context. Arthasastra provides guidance regarding the management of state revenues, tax systems, public expenditures, as well as efficient and responsible financial governance. This research uses a qualitative method with a descriptive-analytical approach, where the Arthasastra text is studied in depth and compared with modern financial policy practices, especially in the context of government and fiscal management in Indonesia. The research results show that many of the financial principles outlined by Kautilya are still relevant, such as the importance of transparency in public financial management, optimizing state revenues through fair taxes, and controlling state expenditure. However, there are several differences in context that require adjustments for application in a modern financial system that is more complex and globally connected. This research also emphasizes the importance of ethics in managing state finances, as outlined by Kautilya, to prevent corruption and improve good governance. Overall, this research concludes that although written in an ancient context, the Arthasastra provides valuable insights for modern financial policy, with several concepts that can still be adapted to improve the effectiveness of state financial management today.